Modernist literature - Potter, Rachel (Rachel C.) (Edinburgh critical guides to literature., 2012)
Introduces students to a wide range of modernist writers and critical debates in modernism studies.. Discussing canonical modernist writers such as James Joyce and T. S. Eliot alongside less familiar writers such as Mina Loy and Djuna Barnes, the guide takes students through a wide-ranging modernist literary landscape. It considers how the publishing networks and collaborative projects which connected writers in the period were central to the creation of English-language modernism. It also introduces students to recent critical debates in modernism studies, with separate chapters on modernism and the writing of geography and exile, the relationship between modernism, obscenity and literary censorship, and modernism and mass culture - with a particular focus on the modernist interest in film - and modernism and politics. The book also considers the changing meaning of the word modernism through twentieth and twenty-first century criticism. Key Features:. Introduces a wide range of modernist writers, including familiar authors such as T. S. Eliot, James Joyce, Ezra Pound and Wyndham Lewis and less canonical figures such as H.D., Mina Loy, Djuna Barnes and Laura Riding Modernism is presented as an extensive literary landscape, something that has featured significantly in recent critical discussions of modernism Introduces students to modernist techniques and to recent debates Shows how English-language modernism emerged, and connects this to recent debates about modernist publishing and networks Key Words:. Modernism, Modernist Literature, Publishing, Obscenity, Censorship, Mass Culture, Politics